Malaysia bloggers participation in political blogs - See, Silk Inn (2015)
New media in Malaysia have successfully turned into an influential political mobilizing tool. Internet became a crucial political battlefield with prominent bloggers fighting as candidates during election and the government appointed “cyber-troopers” to battle against the opposition parties Since then, there are lots of incidents whereby bloggers (blog moderators and blog readers) being penalized by laws due to offensive comments posted. Due to these issues, this study aim to look at how bloggers participate in discussing the political issues in terms of words used, main content discussed by blog moderators,themes emerged from blog readers discussion and process of framing. Besides, there are many researches that focused on blogs and its impacts caused during the election period hence for this study researcher would like to focus on non-election period. In order to conduct this research, qualitative content analysis is applied. Purposive sampling is used to sample blogs and blog posts. Political blogs are selected based on ranking report made by Tecnorati.com and Alexa.com on Malaysia. While, blog posts with the highest number of comments and posted within the same time frame are selected. As a result, based on the criteria listed, anwaribrahimblog.com and sloone.wrodpress.com are the top two political blogs visited by the public and twenty one articles has been identified to be used as research materials. Two trained coders including the researcher coded data for this research. Findings show that there are seven themes emerge from blog readers’ discussion. Ethics and reforms, economy and election are the main categories of issues posted by blog moderators. Besides, there are three types of words used by bloggers, namely juggled words, enforcement of words and short forms. Framework for blog framing shows that bloggers successfully create negative frames towards government.In a nutshell, bloggers utilize political blogs to criticize and to gain political support.